Changes in cortical, cardiac, and respiratory activities in relation to spontaneous rhythmic jaw movements in ketamine‐anesthetized guinea pigs. (21st July 2021) - Yano, Hiroshi; Matsuura, Yutaka; Katagiri, Ayano; Higashiyama, Makoto; Toyoda, Hiroki; Sato, Hajime; Ueno, Yoshio; Uzawa, Narikazu; Yoshida, Atsushi; Kato, Takafumi
Abstract: It has been reported that rhythmic jaw movements (RJMs) spontaneously occur in ketamine‐anesthetized animals. The present study investigated the physiological processes that occur during the cortical, cardiac, and respiratory events which contribute to the genesis of RJMs in animals after supplemental ketamine injections. Fourteen guinea pigs were prepared to allow electroencephalographic, electrocardiographic, and electromyographic activities to be recorded from the digastric muscle, measurement of jaw movements, and nasal expiratory airflow under ketamine‐xylazine anesthesia. Rhythmic jaw movements spontaneously occurred with rhythmic digastric muscle contractions, 23–29 minutes after injection of supplemental ketamine (12.5 and 25.0 mg kg –1, intravenously). The cycle length of RJMs did not differ significantly between the two doses of ketamine (mean±SD: 12.5 mg kg –1, 326.5 ± 60.0 ms; 25 mg kg –1, 278.5 ± 45.1 ms). Following injection of ketamine, digastric muscle activity, heart and respiratory rates, and cortical beta power significantly decreased, while cortical delta and theta power significantly increased. These changes were significantly larger in animals given 25.0 mg kg –1 of ketamine than in those given 12.5 mg kg –1 . With the onset of RJMs, the levels of these variables returned to pre‐injection levels, regardless of the dose of ketamine administered. These results suggest that, following supplemental ketamine injections, spontaneous RJMs occur during a specific period when the pharmacological effects of ketamine wear off, and that these RJMs are characterized by stereotypical changes in cardiac, respiratory, and cortical activities.